Pengaruh Kebijakan Pemerintah RRC Mengenai Muslim Uighur Terhadap Human Security - Muhammad Ashar; Seniwati; Nurjannah Abdullah (Center of Peace, Conflict and Democracy - Hasanuddin University, 2025)
This research analyzes the influence of the People's Republic of China (PRC) government's policies on the Uighur Muslim community in Xinjiang in the context of human security. In recent years, the PRC government has implemented a variety of controversial policies against Uighur Muslims, including mass detention in re-education camps, restrictions on religious practices, and strict surveillance. This research uses a qualitative approach with a case study method to examine the impact of this policy on the human security dimension, which includes personal, political, community, economic and cultural security. The PRC government's policies towards Uighur Muslims not only violate human rights, but also exacerbate overall insecurity at the individual and community levels. These findings underscore the importance of international attention and intervention to address human rights violations and promote human security for the Uighur community in Xinjiang.